2008
DOI: 10.1128/jvi.01383-08
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of Human Immunodeficiency Virus (HIV) Transcription by Formation of Restrictive Chromatin Structures at the Viral Long Terminal Repeat Drives the Progressive Entry of HIV into Latency

Abstract: The molecular mechanisms utilized by human immunodeficiency virus (HIV) to enter latency are poorly understood. Following the infection of Jurkat T cells with lentiviral vectors that express Tat in cis, gene expression is progressively silenced. Silencing is greatly enhanced when the lentiviral vectors carry an attenuated Tat gene with the H13L mutation. Individual clones of lentivirus-infected cells showed a wide range of shutdown rates, with the majority showing a 50% silencing frequency between 30 to 80 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
416
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(439 citation statements)
references
References 55 publications
23
416
0
Order By: Relevance
“…These observations suggest that the lack of expression of the Brm-type SWI/SNF complex would be one of the major causes of the attenuated HIV-1 proviral expression observed in resting CD4 ϩ T cells. In the presence of Tat, stochastic expression patterns of HIV were observed previously by several groups (8,19,(32)(33)(34). For example, it was previously reported by Weinberger et al that Tat stochastics appear to be sufficient to generate phenotypic bifurcation (32).…”
Section: Vol 83 2009mentioning
confidence: 73%
“…These observations suggest that the lack of expression of the Brm-type SWI/SNF complex would be one of the major causes of the attenuated HIV-1 proviral expression observed in resting CD4 ϩ T cells. In the presence of Tat, stochastic expression patterns of HIV were observed previously by several groups (8,19,(32)(33)(34). For example, it was previously reported by Weinberger et al that Tat stochastics appear to be sufficient to generate phenotypic bifurcation (32).…”
Section: Vol 83 2009mentioning
confidence: 73%
“…Host transcription factors (TFs) such as nuclear factor kappa light-chain enhancer of activated B cells (NF-B) have multiple binding sites in the 5= long terminal repeat (LTR) of the HIV-1 genome, and their binding has been demonstrated to be necessary to initiate HIV-1 transcription (6). Sequestration of these TFs in the cytoplasm is one of the mechanisms enabling viral latency (7).…”
mentioning
confidence: 99%
“…Studies have shown that various factors operating at the levels of transcription and posttranscription can restrict the expression of the integrated provirus in resting CD4 ϩ T cells (5,6). Transcriptional blocks to productive HIV-1 replication include epigenetic modifications at the viral long terminal repeat (LTR) and inadequate availability of activation-dependent transcription factors such as P-TEFb, NF-B, NFAT, Sp1, AP-1, and C/EBP (7)(8)(9)(10). Posttranscriptional factors regulating viral latency include inhibition of viral mRNA export to the cytoplasm and regulation of viral gene expression by cellular microRNAs (miRNAs) (11)(12)(13).…”
mentioning
confidence: 99%